ANZSREI consensus statement on elective oocyte cryopreservation. (22nd July 2019) - Lew, Raelia; Foo, Jinny; Kroon, Ben; Boothroyd, Clare; Chapman, Michael; ,
Abstract: Background: One in six Australian women and couples suffer infertility. A rising proportion relates to advanced maternal age, associated with poorer oocyte quality and in vitro fertilisation (IVF) outcomes. Internationally, oocyte cryopreservation technology applied to oocytes vitrified before 35 years provides similar live‐birth statistics compared to IVF treatment using fresh oocytes. Oocyte cryopreservation is accessible in Australasian settings and elective uptake is increasing. For women accessing treatment, oocyte cryopreservation may expand future family building options. Aims: To develop the first Australasian Certification in Reproductive Endocrinology and Infertility (CREI) subspecialist‐led consensus guideline on oocyte cryopreservation. Methods: The ANZSREI ACCEPT (Australasian CREI Consensus Expert Panel on Trial evidence group) met in 2017 and 2018 and identified clinical aspects of care for inclusion and review. Review of the available evidence was conducted and consensus statements prepared. Areas of dissent of expert opinion and for further research were noted. Results: Consensus was reached on definition and best practice in oocyte cryopreservation for freeze method, controlled ovarian stimulation, medical risk reduction and treatment and outcomes counselling. The term 'social egg freezing' may marginalise, stigmatise or attribute social blame to women, and there is a need to revise this to a neutral and non‐judgemental term such as elective or planned oocyte cryopreservation. Conclusion: Oocyte cryopreservation has the potential to improve cumulative live birth outcomes for women. Implementation of this guideline should facilitate an optimal approach for providing care.